(untitled) (Research, Society and Development, 2022)
This article aims to present the role of the teacher in guaranteeing the right to education to children in health treatment, in addition to discussing the importance of the hospital toy library to guarantee the right to play and to promote culture in this context, considering the challenges of these actions in different times. The work of teachers in hospital pedagogical care, at home and in support homes for sick children, and the toys that work in hospital toys, have existed for a long time in Brazil, with specific legislation. Many children during the stages of hospitalization or treatment of the disease, have had their schooling processes interrupted due to the absence of effective public policies for this area and an ignorance of their rights. The majority of the population, however, is still unaware of this right to education, to play, to teachers and jokers. It is necessary, therefore, to discuss these issues, so that the challenges, especially regarding the recognition of this work, are overcome.